A FORMAÇÃO CONTINUDADE DE PROFESSORES QUE ATUAM NO PROEJA NO CONTEXTO DO INSTITUTO FEDERAL DO MARANHÃO (IFMA) - Coutinho, Suzana Andreia Santos (2015)
This research is part of the research group "School Curriculum, Training and Teaching Work," the Federal University of Maranhão. Refers - to the National Professional Education Program Integration with the Basic Education of Youth and Adult Education Mode - PROEJA and aims to analyze the ongoing training of teachers who work in PROEJA of IFMA. In this study it is adopted as a qualitative research methodology, for it is considered that this is important in relation to the researched object, taking into account the objective reality it is in the research under review. We used the literature search, by enabling the researcher to a greater understanding of the researched object, by means of theoretical sources and documentary research, as a theoretical framework based on original documents related to the research without any intervention by the researcher. As research technique adopted the semi-structured interview for data collection. The subjects of the research were two (02) pedagogical coordinators and ten (10) teachers working in the Agricultural Technical ongoing PROEJA totaling a set of twelve (12) individuals surveyed, in order to extract the perceptions of continuing education PROEJA teachers. This research is theoretically based on studies of: Arroyo (1997); Azevedo (2006); Candau (1997); Libâneo (2004); Nóvoa (1991); Paiva (1973); Sacristan (1998); Soares (2007); Triviños (1995); Alves-Mazzotti (2006); Poupart (2010); Haddad (1991); Giroux (1997); Gatti (1997); Freire (2005); Contreras (2002); Althusser (1976); and also documents pertaining to PROEJA. With this study, it was the importance of continuing training for teachers who work in PROEJA, Campus Maracanã, so that they have an increasingly strong background, always looking for the improvement of educational practice in order to develop their teaching activities so achieve student learning, especially those originating from the Youth and Adult Education (EJA). Thus, the research confirms the importance of continuing education, so that they feel more prepared for the classroom everyday with this audience, which has its uniqueness.